Evaluation of intra‐seasonal oscillation simulations in IPCC AR5 coupled GCMs associated with the Asian summer monsoon. (16th March 2017) - Hu, Wenting; Duan, Anmin; He, Bian
ABSTRACT: In this study, we systematically evaluate the intra‐seasonal oscillation (ISO) associated with the Asian summer monsoon region in coupled general circulation models (GCMs) participating in the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5). Results show that most of the models simulate reasonable climatological circulation patterns in boreal summer, but insufficient precipitation over the Bay of Bengal (BOB) and western North Pacific summer monsoon region. Most models underestimate the variance of 12–90‐day ISO mode but overestimate the percent variance of 12–90‐day ISO accounting for raw precipitation anomalies. There remains a wide gap between model simulations and observations in the simulations of eastward‐propagating ISO (30–80‐day), while the models perform better in the northward propagation of the 30–80‐day mode and the westward propagation of the 12–24‐day mode. In addition, mean state circulation, atmospheric internal dynamic process, air–sea interactions and model resolution have varying degrees of impacts on the ISO simulation. The local Hadley and Walker cell biases are investigated in this study, which might relate well with the precipitation bias in models. Within the similar background of vertical easterly shear, few models have the capacity to simulate the equivalent barotropic vorticity to the north of the convection centre. Furthermore, many models have difficulty in reproducing the strong air–sea interactions over the Indian Ocean and the BOB. Our results indicate that simply improving model resolution is not an effective method to obtain more reasonable propagation characteristics of the ISO, especially for eastward propagation. Therefore, further improving the capacity of the ISO simulation remains a great challenge for future development of climate system models.